1977
DOI: 10.1159/000125577
|View full text |Cite
|
Sign up to set email alerts
|

The Visual Cortex during Chronic Stimulation

Abstract: The lateral and suprasylvian gyris of cats have been stimulated anodically by surface electrodes for a total of 40 h by biphasic square waves. Peak currents were ±6.0 mA or 1.0 mA,·to peak. Control electrodes were never stimulated. Electrode materials were low-temperature isotropic carbon and metals (Rh, Pt, Au). Reductions in tissue impedance quickly followed the onset of stimulation. The impedance change was related to stimulus current and to the incidence of motor seizures but not clearly to the electrode m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1977
1977
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…There are only a few reports on neocortical kindling. Moreover, there have been some arguments whether kindling can be developed by stimulations to the visual cortex (Racine, 1975;Harrison and Dawson, 1977). Although it needed more trials and higher intensity of stimulation than amygdaloid kindling, we demonstrated in cats that daily electrical stimulation to the primary visual cortex brought a similar progress of seizure development as in amygdaloid kindling (Baba et al, 1980).…”
mentioning
confidence: 55%
“…There are only a few reports on neocortical kindling. Moreover, there have been some arguments whether kindling can be developed by stimulations to the visual cortex (Racine, 1975;Harrison and Dawson, 1977). Although it needed more trials and higher intensity of stimulation than amygdaloid kindling, we demonstrated in cats that daily electrical stimulation to the primary visual cortex brought a similar progress of seizure development as in amygdaloid kindling (Baba et al, 1980).…”
mentioning
confidence: 55%
“…The impedance of the stimulating electrodes should be periodically monitored as they reflect changes at the electrode-tissue interface due to, for example, the degree of fibrous tissue and bone formation or an increase in the surface area of the electrodes as a result of Pt dissolution (Babb et al 1977;Harrison and Dawson 1977;Agnew et al 1983).…”
Section: Monitoring Impedance In Vivo and In Vitromentioning
confidence: 99%
“…The histological and physiological re sults are reported in companion papers [2,8]. The effect of charge trans fer on selected candidate metallic electrode materials is presented below.…”
Section: Introductionmentioning
confidence: 99%